COLOR IMAGE COMPRESSION USING HYBRID METHOD - Al-Abudi, Bushra; AL-Soufi, Zainab (Iraqi Journal of Science, 2024)
In this work, a new color image compression scheme combining the wavelet transform and modified vector quantization (MVQ) method is proposed. In wavelet transform, the vertical and horizontal Haar filters are composed to construct four 2- dimensional filters, such filters applied directly to the image to speed up the implementation of the Haar wavelet transform. Haar wavelet transform was used to map the image to frequency bands, bit allocation process and scalar quantization are implemented on approximation sub-band while modified vector quantization mechanism employed to encode the other higher frequency subbands using small block size and decrease the codebook size as the subband number increases. Since the encoding process is much easier when the range of coded parameters are positive, thus the coefficients values of codebook are mapped to the positive range. Finally S-Shift encoding process is performed. The analysis results have indicated that the proposed method offers a compression performance up to (29/1) with little effects will be noticed on the image quality.